2014
DOI: 10.1002/asia.201402288
|View full text |Cite
|
Sign up to set email alerts
|

The Microwave‐Assisted Ionic‐Liquid Method: A Promising Methodology in Nanomaterials

Abstract: In recent years, the microwave-assisted ionic-liquid method has been accepted as a promising methodology for the preparation of nanomaterials and cellulose-based nanocomposites. Applications of this method in the preparation of cellulose-based nanocomposites comply with the major principles of green chemistry, that is, they use an environmentally friendly method in environmentally preferable solvents to make use of renewable materials. This minireview focuses on the recent development of the synthesis of nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 76 publications
(189 reference statements)
0
33
0
Order By: Relevance
“…This is due to the restrain effect of cellulose. In the previous study, it was found the restrain effect of cellulose during the synthesis of inorganic materials (Ma, Zhu, Zhu, & Sun, 2014). On the other hand, the effect of the ionic radius may result in the failure synthetic.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the restrain effect of cellulose. In the previous study, it was found the restrain effect of cellulose during the synthesis of inorganic materials (Ma, Zhu, Zhu, & Sun, 2014). On the other hand, the effect of the ionic radius may result in the failure synthetic.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 15 exhibits the XRD pattern of the PC and its cationic derivatives. The characteristic peaks of PC and insoluble CPC are observed in the diffractions of 16.0°, 22.5°, and 34.7°, which can be indexed to cellulose I crystal [45][46][47]. In comparison with the diffraction pattern of original cellulose, the diffraction pattern of insoluble CPC shows a decrease in intensity and a broadening of peak at 2θ = 22.5°.…”
Section: Effect Of Microwave Irradiation On the Viscosity Of Cpcmentioning
confidence: 89%
“…Moreover, compared to the traditional in vacuo manner, reactive distillation improved the glycerol conversion of 29.1% and saved in energy consumption by 37.1%, accordingly. Importantly, the interesting microwave irradiation technology has been developed and employed in various procedures, like chemical reaction [71,72], material synthesis [73], nanotechnology [74] and biochemical processes [75,76]. It is noteworthy that microwave would improve the product yield and shorten the reaction time in producing carbonates from CO 2 and epoxide [77], NaHCO 3 and olefins [78], CO and diols [79], and polycarbonates from open-ring polymerization of trimethylene carbonate [80].…”
Section: Reaction With Zinc-based Catalyst As Depicted Inmentioning
confidence: 99%